New sufficient conditions for the solvability of a new class of Sylvester-like absolute value matrix equation - Kumar, Shubham; Deepmala; Keshtwal, Roshan Lal (J. Numer. Anal. Approx. Theory, 2023)
In this article, some new sufficient conditions for the unique solvability of a new class of Sylvester-like absolute value matrix equation \(AXB - CXD =F\) are given. This work is distinct from the published work by Li [Journal of Optimization Theory and Application, 195(2), 2022]. Some new conditions were also obtained, which were not covered by Li. We also provided an example in support of our result.